Analytical toxicology for clinical, forensic, and pharmaceutical chemists - Brandenberger, H.; Maes, R. A. A. 1937- (Clinical biochemistry ;, 1997)
Aimed at toxicologists and pharmacists involved in analytical work, this text provides critical evaluations of analytical possibilities to help with the choice of methods.